Numerical and Experimental Analysis of the Fracture Behaviour of Heterogeneous Welded Structures - Kozak, Dražan; Gubeljak, Nenad; Sedmak, Aleksandar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this book, modern trends in testing and simulating heterogeneous welded joints, including multi-scale approaches, resulting in appropriate flaw assessment procedures, are highlighted and discussed. The eleven research papers presented in this book give some overview of recent analytical, numerical, and experimental investigations in the field of yield strength mismatched welded joint behaviour. The papers cover several important issues to more accurately characterise the fracture mechanics behaviour and structural integrity assessments.